The Effect of Education, Training and Competence on The Performance Teachers in Kabupaten Musi Rawas - Choiriyah, Choiriyah; Idris, Muhammad; Monas, Satrio; Ulpa, Fithri Atika (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study aims to determine the Effect of Education, Training, and Competence on the Performance of Junior High School Teachers in Muara Lakitan District, Musi Rawas Regency. This type of research is quantitative descriptive. The sample in this study was 105 junior high school teachers in Muara Lakitan District, Musi Rawas Regency. This study used primary and secondary data sources. The study results indicate that education, training, and competence together affect the performance of junior high school teachers in Muara Lakitan District, Musi Rawas Regency. The hypothesis in this study indicates that Ho is rejected. Education involves the performance of junior high school teachers in Muara Lakitan District, Musi Rawas Regency. This is because Ho is rejected. Training affects the performance of junior high school teachers in Muara Lakitan District, Musi Rawas Regency. This is indicated by Ho being rejected. Competence affects the performance of junior high school teachers in Muara Lakitan District, Musi Rawas Regency. This is evidenced by the hypothesis in the study Ho, which is rejected